Review of Quantitative Methods for Designing Availability-Based Contracts. Issue 1 (2nd January 2016) - Kashani Pour, Amir Reza; Sandborn, Peter; Cui, Qingbin
Abstract : Understanding the total life-cycle cost is an essential part of all sustainment contracts. Sustainment constitutes 70% or more of the total life-cycle cost of safety-, mission-, and infrastructure-critical systems. For many types of systems, availability is the most critical factor in determining the total life-cycle cost of the system. To address this, availability-based contracts have been introduced in the governmental and non-governmental acquisitions space (e.g., energy, defense, transportation, and healthcare). As a result, in the new service-oriented environment, formulating contracts in cost effective ways (for both the customer and the contractor) is of great importance for pricing, negotiations, and transparency. Meanwhile, the development, implementation, and impact of contract and availability requirements within contracts is not well understood. This article reviews quantitative studies that address the critical elements for designing availability-based contracts. Assessments of current methodologies ranging from optimization- to simulation-based methods in domains of practice that utilize availability-based contracts are included, and research gaps are identified.